Biogas production from brown grease using a pilot-scale high-rate anaerobic digester - Zhang, Pengchong; Lin, Che-Jen; Liu, James; Pongprueksa, Pruek; Evers, Simon A.; Hart, Peter (Renewable energy, 2014)
Food wastes are typically disposed of in landfills for convenience and economic reasons. However, landfilling food wastes increases the organic content of leachate and the risk of soil contamination. A sound alternative for managing food wastes is anaerobic digestion, which reduces organic pollution and produces biogas for energy recovery. In this study, anaerobic digestion of a common food waste, brown grease, was investigated using a pilot-scale, high-rate, completely-mixed digester (5.8 m3). The digestibility, biogas production and the impact of blending of liquid waste streams from a nearby pulp and paper mill were assessed. The 343-day evaluation was divided into 5 intensive evaluation stages. The organic removal efficiency was found to be 58 ± 9% in terms of COD and 55 ± 8% in terms of VS at a hydraulic retention time (HRT) of 11.6 ± 3.8 days. The removal was comparable to those found in organic solid digesters (45–60%), but at a much shorter HRT. Methane yield was estimated to be 0.40–0.77 m3-CH4@STP kg-VSremoved−1, higher than the typical range of other food wastes (0.11–0.42 m3-CH4@STP kg-VSremoved−1), with a mean methane content of 75% and <200 ppm of hydrogen sulfide in the biogas. The blending of selected liquid wastes from a paper mill at 10 vol% of brown grease slurry did not cause significant reduction in digester performance. Using a pseudo-first-order rate law, the observed degradation constant was estimated to be 0.10–0.19 d−1 compared to 0.03–0.40 d−1 for other organic solids. These results demonstrate that brown grease is a readily digestible substrate that has excellent potential for energy recovery through anaerobic digestion. •A pilot-scale two-stage anaerobic digester was applied to treat waste brown grease.•Kinetic analysis showed that brown grease is a readily digestible substrate.•Digestion of brown grease produced high-quality bio-methane (∼75% CH4).•High methane yield suggested that the process could be profitable.•Introduction of liquid co-substrate optimized system cost and efficiency.